Where to locate tax employees? The role of tax complexity and tax risk implications - Henning Giese; Reinald Koch; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2024)
This study analyzes the impact of tax complexity on the location of tax employees and tax risk. Using a hand-collected dataset of more than 7,500 tax employees from 348 European-listed multinationals, we identify two types of firm-level costs associated with tax complexity-tax employees, and tax risk. We find that firms locate more tax employees in countries with greater tax complexity. This association is particularly pronounced for complexity in tax procedures. We also find that multinationals operating in countries with high tax complexity are associated with higher tax risk. The incremental tax risk vanishes for firms that locate more tax employees in countries with highly complex tax procedures, while we find no risk reduction from additional tax employees in countries with complex tax rules. Our results reveal that multinationals eliminate 25 percent of overall tax complexity-related tax risk through targeted location of tax employees.
Keywords: H25; H26; M12; 330; tax complexity; tax complexity cost; tax department; tax employees; tax risk